Impact of mobility on QoS of mobile WiMAX network / Nur Fadilah A.Bakar - A.Bakar, Nur Fadilah (2016)
WiMAX or better known as World Interoperability for Microwave Access provides an innovative fixed as well as mobile platform for broadband internet access. Mobile WiMAX has been designed to support wide range of applications including VOIP (Voice over Internet Protocol).VoIP is a technology for the transmission of voice and multimedia over the Internet Protocol based network. In this study, OPNET 14.5 is used to simulate the Mobile WiMAX network as it can provide the real life platform of network environment. The goal of this study is to investigate the impact of mobility on VoIP application. The voice codecs of G.711 and G.729A have been chosen as it can perform well under UGS class. The performance matrices used for the evaluation are throughput, end-to-end delay, jitter and MOS value. The results of deploying the voice codec using different speeds and multipath channel models have been compared. From the simulated results, it shows that G.711 can serve VoIP application better than G.729A. Furthermore, variation of speeds in Mobile WiMAX does not have any significant effects and VoIP still can be supported at 100 km/h rate.